Runaway electron generation and loss in EAST disruptions. (13th May 2021) - Tang, T.; Zeng, L.; Chen, D.; Sun, Y.; Zhao, H.; Zhou, T.; Ti, A.; Lin, S.; Zhou, R.; Zhu, X.; Qian, J.; Liu, H.; et al.
Abstract: Runaway currents have been detected during unintended disruptions in the circular plasma with the limiter configuration in the Experimental Advanced Superconducting Tokamak (EAST). The runaway electron (RE) plateau can carry up to 80% of the pre-disruption plasma current. The highest runaway currents correspond to the lowest loop voltage, which is contrary to the observations made in most tokamaks. This anomalous behavior is attributed to the acceleration of the pre-existing wave resonant suprathermal electrons by lower hybrid waves during the disruption decay phase. Two distinct types of RE-related relaxation phenomena, distinguished on the basis of the amplitude of the magnetic fluctuations, have been found during the disruptions. Large-amplitude magnetohydrodynamic activity with indications of RE loss is observed during the RE plateau when the edge safety factor decreases to less than 3, and the external kink mode is discussed to resolve this anomaly. Burst-like relaxations with small-amplitude magnetic fluctuations and ∼0.6 kHz frequency are confirmed from the spikes in the hard x-ray array signals under a negative loop voltage. Measurement of the RE energy distribution suggests that the instability is driven by medium-energy REs.